STUDI KOMPARATIF PENGGUNAAN METODE CAMEL SEBAGAI ALAT PENGUKUR KINERJA BANK UMUM KONVENSIONAL DAN BANK UMUM SYARIAH - Iwan Efriandy; Muhammad Wadud (Universitas Indo Global Mandiri)
The purpose of this study was to determine the difference and analyze financial performance and conventional banks Islamic banks. Type approach in this study is the quantitative approach. The research location is a conventional bank and Islamic banks are in Prabumulih. The research design used in this study was a descriptive study and research is quite descriptive comparative study, a study that is looking at or comparing the performance difference with conventional banks and Islamic banks using the CAMEL. The data used in this research is secondary data and primary data. Source data from conventional banks and Islamic banks, in the form of financial ratios in the quarterly financial statements and annual bank. The financial statements used in this study is a three-year financial statements, which 2012-2014.Teknik years of data analysis used in this research is the analysis of financial ratios (financial ratio analysis), the proxy CAMEL (capital, assets, management, earnings, liquidity and sensitivity to market risk). Analysis of financial ratios related to the financial performance of the bank group. This analysis is based on quantitative data is data in the form of figures on the bank's financial statements. Key words: Leadership, Competence, Career Development, and Performance, Apparatus